IMPLEMENTATION OF FOCUS GROUP DISCUSSION (FGD) BASED INFORMATION SERVICES IN PREVENTING DOMESTIC VIOLENCE - Ica Parhati; Suryati; Putra, Belajanare (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This study is entitled